2015
DOI: 10.1074/jbc.m115.649004
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-542-3p Suppresses Tumor Cell Invasion via Targeting AKT Pathway in Human Astrocytoma

Abstract: Background: MicroRNAs play important roles in regulating AKT pathway. Results: miR-542-3p suppresses glioblastoma cell invasion through directly inhibiting AKT1, ILK, and PIK3R1. Conclusion: miR-542-3p down-regulation contributes to aberrant activation of the AKT signaling, and miR-542-3p acts as a negative regulator in astrocytoma progression. Significance: Learning how miRNAs participate in AKT pathway is crucial for understanding its regulators and cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 42 publications
3
28
0
Order By: Relevance
“…The present study showed that PI3K inhibitor (LY294002) suppressed the PI3K/AKT/survivin signal and increased the anticancer effects of miR-542-3p on apoptosis in colon cancer. Cai et al found that miR-542-3p suppressed the tumor cell invasion of human astrocytoma via targeting the AKT pathway (21).…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that PI3K inhibitor (LY294002) suppressed the PI3K/AKT/survivin signal and increased the anticancer effects of miR-542-3p on apoptosis in colon cancer. Cai et al found that miR-542-3p suppressed the tumor cell invasion of human astrocytoma via targeting the AKT pathway (21).…”
Section: Discussionmentioning
confidence: 99%
“…miR-7 directly targets PI3K [114]. The downstream Akt is targeted by miR-542-3p [115]. miR-21 indirectly regulates PI3K through targeting its antagonist PTEN [116].…”
Section: Mirna Modulates Glucose Metabolism and Glycolysis Related Simentioning
confidence: 99%
“…Furthermore, PTEN is targeted by miR-221/222, clustered in Xp11.3, which is found to be upregulated in high relative to low WHO grade glioma [ 95 , 134 ]. Additionally, the expression of the PI3K downstream effector, Akt (specifically Akt1 ), is regulated by miR-542-3p which is found to be downregulated in GBM [ 135 ]. miR-542-3p is negatively correlated with glioma WHO grade and is associated with poor prognosis [ 135 ].…”
Section: Mirna Regulation Of Rtks and Their Downstream Effector Pamentioning
confidence: 99%